Lands of majesty the Americas - Geockel, Brrendan ([S.l.] : JWM Productions, 2000)
Travel the Americas to explore four of the world's most beautiful National Parks.
Executive producer, Wendy Maples ; editor, Jennifer Beman White
Narrator: Nigel Anthony
Keywords: National parks and reserves -- United States; Wildlife conservation